THE SOCIALIZATION PROCESS OF PROSTITUTION:A CASE STUDY IN AN INDONESIAN REGENCY PRIMARY SOURCE OF PROSTITUTES - - Koentjoro (Jurnal Psikologi, 1997)
This research sets out to understand socialization of prostitution in the rural areas of indonesia. This  study seeks answers how and why socialization occurs in that community and factors which can be identified as contributing significantly to socialization of prostitution.